Gladiatorial Spectacles in Crete - Karambinis, Michalis (Tekmeria, 2023)
This article examines the epigraphic and archaeological evidence attesting the staging of gladiatorial and associated spectacles in Roman Crete. The evidence indicates shows held in the capital of the province, Gortyn; in the colony of Knossos, in Hierapytna, and possibly in Chersonesos and Kissamos. Some of the spectacles that took place in Gortyn were extraordinary and very costly, including beast fights, public executions and gladiatorial combats with sharp weapons. The cities that presented these spectacles were leading towns and principal ports for the complex trade networks in which the island was involved, and open to innovation. The wealth thereby accumulated enabled the execution of new public infrastructures in these towns, among them the new type of spectacle building that appeared in the Mediterranean, the amphitheater.